Conflits Autour De L’exploitation Halieutique Du Fleuve Comoé Et De Ses Affluents - Sosthène, Aka Koffi (European Scientific Journal, ESJ, 2017)
The purpose of this article is to identify the conflicts arising from the exploitation of the ComoÃ© River. CÃ´te d’Ivoire has a dense hydrography which is distinguished by four main rivers of which the ComoÃ© River (1160 km) is one of them. This river area, which has always been exploited by the various villages bordering it, is perceived by the latter as their property. Thus, they ensure customary management in accordance with marked territories. The immense benefits of this river to village communities sometimes give rise to tensions and conflicts. What are the causes of these different types of conflicts with regards to the ComoÃ© River? In other words, what are the conditions for their gestation? The objective of this study is to reveal the conflicts surrounding the fisheries exploitation of the ComoÃ© River and to propose solutions for a sustainable fishery. This study is based on desk research and land surveys. It appears from the above that the exploitation of the aquatic area of the ComoÃ© River generates sporadic conflicts. These conflicts arise mainly because of a poor implementation of the clauses of the contract between indigenous and non-native fishers, dominated by the monthly fee and the unhealthy practices of the actors. The management of these oppositions of interests is ensured by a traditional regulation, coupled with that of the administration when the situation is of great magnitude.